Risk of fetal loss after chorionic villus sampling in twin pregnancy derived from propensity score matching analysis. (13th January 2022) - Gil, M. M.; Rodríguez‐Fernández, M.; Elger, T.; Akolekar, R.; Syngelaki, A.; De Paco Matallana, C.; Molina, F. S.; Gallardo Arocena, M.; Chaveeva, P.; Persico, N.; Accurti, V.; Kagan, K. O.; et al.
ABSTRACT: Objective: To estimate the risk of fetal loss associated with chorionic villus sampling (CVS) in twin pregnancy, using propensity score analysis. Methods: This was a multicenter cohort study of women with twin pregnancy undergoing ultrasound examination at 11–13 weeks' gestation, performed in eight fetal medicine units in which the leadership were trained at the Harris Birthright Research Centre for Fetal Medicine in London, UK, and in which the protocols for screening, invasive testing and pregnancy management are similar. The risk of death of at least one fetus was compared between pregnancies that had and those that did not have CVS, after propensity score matching (1:1 ratio). This procedure created two comparable groups by balancing the maternal and pregnancy characteristics that lead to CVS being performed, similar to how randomization operates in a randomized clinical trial. Results: The study population of 8581 twin pregnancies included 445 that had CVS. Death of one or two fetuses at any stage during pregnancy occurred in 11.5% (51/445) of pregnancies in the CVS group and in 6.3% (515/8136) in the non‐CVS group ( P  < 0.001). The propensity score algorithm matched 258 cases that had CVS with 258 non‐CVS cases; there was at least one fetal loss in 29 (11.2%) cases in the CVS group and in 35 (13.6%) cases in the matched non‐CVS group (odds ratio (OR), 0.81; 95% CI, 0.48–1.35; P  = 0.415). However, there was a significant interaction between the risk of fetal loss after CVS and the background risk of fetal loss; when the background risk was higher, the risk of fetal loss after CVS decreased (OR, 0.46; 95% CI, 0.23–0.90), while, in pregnancies with a lower background risk of fetal loss, the risk of fetal loss after CVS increased (OR, 2.45; 95% CI, 0.95–7.13). The effects were statistically significantly different ( P ‐value of the interaction = 0.005). For a pregnancy in which the background risk of fetal loss was about 6% (the same as in our non‐CVS population), there was no change in the risk of fetal loss after CVS, but, when the background risk was more than 6%, the posterior risk was paradoxically reduced, and when the background risk was less than 6%, the posterior risk increased exponentially; for example, if the background risk of fetal loss was 2.0%, the relative risk was 2.8 and the posterior risk was 5.6%. Conclusion: In twin pregnancy, after accounting for the risk factors that lead to both CVS and spontaneous fetal loss and confining the analysis to pregnancies at lower prior risk, CVS seems to increase the risk of fetal loss by about 3.5% above the patient's background risk. © 2021 International Society of Ultrasound in Obstetrics and Gynecology. Abstract : Linked article: There is a comment on this article by Li and Li. Click here to view the Correspondence. This article's abstract has been translated into Spanish and Chinese. Follow the links from the abstract to view the translations. RESUMEN: Riesgo de muerte fetal tras una biopsia de vellosidades coriónicas en el embarazo de gemelos derivado del análisis de pareamiento por puntaje de propensión Objetivo: Estimar el riesgo de muerte fetal asociado a la biopsia de vellosidades coriónicas (BVC) en el embarazo de gemelos, mediante un análisis de pareamiento por puntaje de propensión. Métodos: Este fue un estudio de cohortes multicéntrico de mujeres con embarazo de gemelos que se sometieron a un examen ecográfico a las 11–13 semanas de gestación, realizado en ocho unidades de medicina fetal en las que la gerencia se formó en el Harris Birthright Research Centre for Fetal Medicine de Londres (Reino Unido), en las cuales los protocolos de cribado, pruebas agresivas y la atención médica al embarazo son similares. Se comparó el riesgo de muerte de al menos un feto entre los embarazos a los que se les practicó la BVC y los que no se les practicó, tras un pareamiento por puntaje de propensión (relación 1:1). Este procedimiento creó dos grupos comparables en los que las características de la madre y el embarazo que se asocian con la BVC estaban equilibradas, de manera similar a cómo funciona la aleatorización en un ensayo clínico aleatorizado. Resultados: La población del estudio fue de 8581 embarazos de gemelos e incluyó 445 a los que se les practicó una BVC. La muerte de uno o dos fetos en cualquier fase del embarazo se produjo en el 11, 5% (51/445) de los embarazos en el grupo con BVC y en el 6, 3% (515/8136) en el grupo sin BVC (P<0, 001). El algoritmo del puntaje de propensión emparejó 258 casos a los que se les practicó una BVC con 258 casos sin BVC; hubo al menos una muerte fetal en 29 (11, 2%) casos del grupo con BVC y en 35 (13, 6%) casos del grupo emparejado sin BVC (razón de momios [RM], 0, 81; IC 95%, 0, 48–1, 35; P=0, 415). Sin embargo, hubo una interacción significativa entre el riesgo de muerte fetal después de la BVC y el riesgo previo de muerte fetal; cuando el riesgo previo era mayor, el riesgo de muerte fetal después de la BVC disminuyó (RM, 0, 46; IC 95%, 0, 23–0, 90), mientras que en los embarazos con un riesgo previo de muerte fetal menor, el riesgo de muerte fetal después de la BVC aumentó (OR, 2, 45; IC 95%, 0, 95–7, 13). Los efectos fueron significativamente diferentes desde el punto de vista estadístico (valor P de la interacción=0, 005). Para un embarazo en el que el riesgo previo de muerte fetal era de aproximadamente el 6% (el mismo que en la población sin BVC), no hubo ningún cambio en el riesgo de muerte fetal tras la BVC, pero, cuando el riesgo previo era superior al 6%, el riesgo posterior se redujo, paradójicamente, y cuando el riesgo previo era inferior al 6%, el riesgo posterior aumentó exponencialmente; por ejemplo, si el riesgo previo de muerte fetal era del 2, 0%, el riesgo relativo era del 2, 8 y el riesgo posterior fue del 5, 6%. Conclusión: En los embarazos de gemelos, después de tener en cuenta los factores de riesgo que conducen tanto a la BVC como a la pérdida espontánea del feto y limitando el análisis a los embarazos con un riesgo previo menor, la BVC parece aumentar el riesgo de pérdida del feto en aproximadamente un 3, 5% por encima del riesgo previo de la paciente. © 2021 International Society of Ultrasound in Obstetrics and Gynecology. 摘要: 从倾向度匹配分析获得双胎妊娠中绒膜绒毛取样后妊娠丢失的风险 目的: 采用倾向度分析，估计双胎妊娠中绒膜绒毛取样(CVS)相关的妊娠丢失风险。 方法: 这是一项多中心人群队列研究，研究对象包含在八家胎儿医学中心进行超声检查的孕11‐13周双胎妊娠妇女。这些医学中心的领导层都曾在英国伦敦的哈里斯胎儿医学出生权利研究中心(Harris Birthright Research Centre for Fetal Medicine)接受过培训，其筛查、侵入性检查及妊娠管理医疗方案均类似。至少一胎死亡的风险在倾向度匹配(1:1比率)后在进行和未进行CVS的妊娠之间进行了比较。通过比较致使进行CVS的产妇特征及妊娠特征，类似于随机化在随机临床试验中操作，该程序创建了两个可比组。 结果: 本研究人群共8581例双胎妊娠，含进行过CVS的445例。在妊娠期任何阶段有一胎或双胎死亡的，在CVS组中有11.5%(51/445)，在未进行CVS组中有6.3%(515/8136)(P<0.001)。倾向度算法配对了进行过CVS的258例和未进行过CVS的258例；在CVS组中至少一胎妊娠丢失的有29例(11.2%)，而在配对的未进行CVS组中有35例(13.6%)(比值比(OR)，0.81；95%CI，0.48–1.35，P=0.415)。然而，在CVS之后妊娠丢失风险与妊娠丢失的背景风险之间有显著的相互影响；当背景风险较高时，CVS后妊娠丢失的风险下降(OR，0.46；95%CI，0.23–0.90)，而在妊娠丢失背景风险较低的妊娠中，妊娠丢失风险在CVS后增加(OR，2.45；95%CI，0.95–7.13)。该影响在统计学上有显著差异(相互影响的P值=0.005)。对于妊娠丢失背景风险在6%左右的妊娠(在我们未进行CVS的人群中也是一样)，CVS后妊娠丢失风险没有变化，但是当妊娠丢失背景风险在6%以上时，事后风险反常地减少了，而当妊娠丢失背景风险小于6%时，事后风险却成倍增加；例如，如妊娠丢失的背景风险是2.0%，相对风险为2.8，事后风险为5.6%。 结论: 在双胎妊娠中，在解释了导致CVS和自然妊娠丢失的风险因素之后，并将分析局限在先前风险较低的妊娠，CVS似乎将妊娠丢失风险在患者的背景风险之上增加了3.5%左右。© 2021年国际妇产科超声学会。